PENGARUH INDEKS PEMBANGUNAN GENDER DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP KEMISKINAN 15 PROVINSI DI INDONESIA - Sari Berutu, Nova; Asnawi, Asnawi; Roni, Muhammad (LPPM UNIMAL, 2025)
Poverty is one of the major problems for developing countries. Some theories say that the quality of human resources can be the main factor causing poverty. The quality of human resources can be seen from the Human Development Index (HDI). In this study, we want to know the influence of the Gender Development Index and Human Development Index on poverty in 15 provinces in Indonesia. This study uses a combination of cross section data with time series in 15 provinces in Indonesia during 2018-2022. The data analysis method used is Panel Data Regression with the help of Eviews 12. The results of this study prove that the Gender Development Index has no positive and significant effect on poverty. The Human Development Index has a negative effect on poverty as well.